New low polar tolane cholesterics designed for infrared applications. Issue 87 (6th September 2016) - Herman, Jakub; Kula, Przemysław
Abstract : We have designed, synthesized and evaluated the physical properties of new fluorinated phenyltolane based chiral liquid crystal materials with 2-methylbutyl terminal chain. Abstract : We have designed, synthesized and evaluated the physical properties of new fluorinated phenyltolane based chiral liquid crystal materials with 2-methylbutyl terminal chain. The 2- or 2, 6-fluorosubstitution in combination with the phenyltolane core brings surprising improvement of mesomorphic properties. The investigated compounds are characterized by a broad temperature range of the cholesteric (chiral nematic N*) phase, very low melting temperatures and easy thermal control of selective reflection in the near infrared region. The moderate helical twisting power β, high optical anisotropy and source of a blue phase make these compounds attractive for cholesteric mixture formulations.